Customer Relationship Management Strategy for Enhancing Customer Loyalty at MM Beauty Clinic Using the K-Means Algorithm - Hazlita Hazlita; Hafizhah Mardivta; Aysyah Rengganis (Universitas Nurul Jadid, 2026)
MM Beauty Clinic is one of the beauty service providers in North Sumatra Province that still carries out most of its service processes manually. This condition has the potential to reduce service quality and increase the risk of customers switching to other clinics. This study aims to design and implement a web-based Customer Relationship Management (CRM) system to strengthen customer loyalty. The system was developed using the PHP programming language and a MySQL database. The approach used is Recency, Frequency, and Monetary (RFM) analysis combined with the K-Means algorithm to segment customers based on their transaction patterns. The data used are patient transaction data for April 2026. The segmentation results are used as the basis for determining appropriate service strategies for each customer group. The implementation of this CRM system is expected to improve the effectiveness of customer relationship management, as well as facilitate transaction processing, consultation services, complaint submission, and access to service information more quickly, effectively, and efficiently.